Critical Thinking Elementary Students Related Digestive System Material in Humans through Learning Problem Posing - Wati, Rida Rosiana; Sa'ud, Udin Saefudin; Sopandi, Wahyu; Sujana, Atep (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This research is conducted on the basis of low critical thinking ability of elementary school students, especially in SCIENCE learning. The purpose of this research is to see the influence of Problem Posing model on critical thinking ability. Learning Problem Posing is a lesson-based learning question, that is, students ask questions based on the situation given by the teacher. This method of research is a quasi experimental design of one group Pretests posttest design, with the research samples of 24 grade V students from SDN Corenda of Cisitu subdistrict. Consisting of 10 female students and 14 male students. The instruments used are tests. Tests conducted in two stages, namely pretests and posttest with the number of 15 questions shaped essay. Data processing techniques using SPSS program version 23. The results showed that the average posttest scores critical of students using problems posing higher than pretest. So it can be concluded that learning SCIENCE with problems